A Comparison of the Dung Beetle (Coleoptera: Scarabaeidae: Scarabaeinae) Collecting Performance of Pitfall Traps and Burrowing Interception Traps - Goh, Thary Gazi; Hashim, Rosli (Coleopterists Society, 2018)
A method for trapping dung beetles by preventing the beetles from burrowing out of a container is described and illustrated. The trap consists of dung bait placed directly in contact with soil within a plastic container. Beetles are prevented from burrowing further into the ground by the container and become trapped. The soil with the trap is then manually inspected for the beetles trapped within. Compared to conventional pitfall traps, this method collects a higher abundance of tunnelling dung beetles. Beetles inside the trap are collected alive, which makes this trap suitable for DNA and population studies. However, while this trap is more effective with tunneler dung beetles, it is less effective for collecting roller dung beetles than conventional pitfall traps. This method has potential uses in studies of dung beetle behavior, taxonomy, and ecology.